A Film Study of Loneliness. About “Tatarak” by Andrzej Wajda - Małgorzata Okupnik (Forum Oświatowe, 2014)
Andrzej Wajda has often taken up the topic of loneliness. In the screen adaptation of “Tatarak” (2009) he showed the loneliness of a married couple in the face of death and serious illness. The director used two stories: “Tatarak” by J. Iwaszkiewicz and “The sudden call” by S. Marai. The most important plot of the film is the private confession of the actress Krystyna Janda, who had recently lost her husband. In the analysis of the film by Wajda the philosophical concept mimesis may be used. Paul Ricoeur in “Time and Narration” claims that mimesis is not a homogeneous category and distinguishes three variations of it. Behind the three types of mimesis of “Tatarak,” lie different meanings of loneliness. In mimesis III two worlds overlap: the world of the artist and the world of the audience. Janda’s narration leads to an active understanding of what the experience of loss and loneliness is and crystallizes it. The story about loss and loneliness is also a form of therapy for her.